Isotypic equivalence of Abelian p-groups with separable reduced parts - Bunina, Elena (Sarajevo Journal of Mathematics, 2024)
We prove that two Abelian p-groups with separable reduced parts are isotypically equivalent if and only if their divisible parts and their basic subgroups are elementarily equivalent. Also as a corollary we prove that any Abelian p-group with a separable reduced part is ω-strongly homogeneous